Chewing lice of the genus Myrsidea (Phthiraptera: Menoponidae) from New World warblers (Passeriformes: Parulidae) from Costa Rica, with descriptions of four new species - Kounek, Filip; Sychra, Oldrich; Capek, Miroslav; Literak, Ivan (Zootaxa, 2011)
Four new species of chewing lice of the genus Myrsidea parasitic on members of the avian family Parulidae are described. They and their type hosts are: Myrsidea basileuteri ex Basileuterus rufifrons, M. myiobori ex Myioborus miniatus, M. paleno ex Parkesia motacilla and M. zeledoni ex Phaeothlypis fulvicauda. Records of undescribed Myrsidea representing new louse-host associations for Basileuterus tristriatus and Parula pitiayumi are also discussed.